High resolution nested runs of the AURAMS model with comparisons to PrAIRie2005 field study data - Makar, Paul A.; Stroud, Craig; Wiens, Brian; Cho, Sunflee; Zhang, Junhua; Sassi, Morad; Liggio, John; Moran, Michael; Gong, Wanmin; Sunling Gong; Li, Shao-Meng; Brook, Jeff; et al. (AIR POLLUTION MODELING AND ITS APPLICATION XIX, 2008)
The PrAIRie2005 campaign took place in the summer of 2005 in the city of Edmonton, Alberta. The measurement campaign was designed and led by air-quality modellers with the scientific objective of determining the extent to which air pollution events in the city are the result of locally emissions versus long-range transport. A nested version of the AURAMS model was constructed for post-campaign simulations and evaluation against the measurement data. The nested model runs at different resolutions, the highest of which is a 3 km horizontal resolution centered on the urban area. The high resolution model results show good agreement with observations, with side-by-side sampling through the real and model atmosphere. The comparison shows the same features for particle composition (Aerodyne AMS measurements compared to speciated PM1), for airborne gases (continuous NO, NO2, O-3) and ground-based measurements of gases, particle composition and particle layering structure. The simulations reveal that air-quality in the Edmonton area is complex, largely due to multiple local sources, with occasional long-range-transport events.